Asymptotic methods of nonlinear mechanics as applied to nonlinear differential equations with delayed argument - Mitropolsky, Y. A.; Fоdchuk, V. I.; Митропольский, Ю. А.; Фодчук, В. И. (Institute of Mathematics, NAS of Ukraine, 1966)
-